Fatal Septicemia Caused by the Zoonotic Bacterium Streptococcus iniae During an Outbreak in Caribbean Reef Fish. (September 2014) - Keirstead, N. D.; Brake, J. W.; Griffin, M. J.; Halliday-Simmonds, I.; Thrall, M. A.; Soto, E.
An outbreak of Streptococcus iniae occurred in the early months of 2008 among wild reef fish in the waters of the Federation of St Kitts and Nevis, lasting almost 2 months. Moribund and dead fish were collected for gross, histological, bacteriological, and molecular analysis. Necropsy findings included diffuse fibrinous pericarditis, pale friable livers, and serosal petechiation. Cytological and histological analysis revealed granulocytic and granulomatous inflammation with abundant coccoid bacterial organisms forming long chains. Necrosis, inflammation, and vasculitis were most severe in the pericardium, meninges, liver, kidneys, and gills. Bacterial isolates revealed β-hemolytic, Gram-positive coccoid bacteria identified as S . iniae by amplification and 16S ribosomal RNA gene sequencing. Results from biochemical and antimicrobial susceptibility analysis, together with repetitive element palindromic polymerase chain reaction fingerprinting, suggest that a single strain was responsible for the outbreak. The inciting cause for this S . iniae –associated cluster of mortalities is unknown.